Avaliação do potencial osteogênico de células de sangue de cordão umbilical humano e periósteo de ratos e do potencial osteocondutor de xenoenxerto bovino na terapia de perdas ósseas - Silva, Igor Iuco Castro da (2008)
The repair of extensive bone loss still represents a great challenge in modern Medicine. New alternatives appear to provide this claim, among this, the use of cell therapies to obtain directelly bone tissue or by acellular bone substitutes biomaterials, as xenografts. The major aim of this study was to evaluate the osteogenic potential of human umbilical cord blood (h-UCB) and rat periosteum (r-P) cells and verify the osteoconductive efficacy of the use of a xenograft for bone loss therapy. To performe this study we used in vitro and in vivo assays. The in vitro assay was divided in two steps where in step 1 the cells were harvested and cultivated of h-UCB and r-P. In the step 2, the platement of pos-expansion cells (passage 2) was achieved in order to accompany the differentiation of cells in osteoblasts and mineralized matrix formation, using qualitative (morphologic analysis and citochemistry/Von Kossa) and quantitative parameters (calcium and alkaline phosphatase assay) at experimental times 7, 14, 21 e 28 days an upon apropriated conditions of osteogenic medium (dexamethazone, ascorbic acid and betaglycerophosphate). At in vivo study, a critical size defect (8 mm of diameter) was created in the skull of Wistar rats (n=50) and treated according the following groups: blood clot (Group 1), autogenous bone graft (Group 2) and noncellular xenograft made up bovine hydroxyapatite and collagen I (Group 3). Macroscopic, radiographic and histopathologic evaluations of necropsied samples were achieved in 0, 7, 30 and 90 days after surgery. The data in vitro confirm osteodifferentiation process from r-P cells since 14 days and from h-UCB since 21 days. The data in vivo show that although no treatment promoted the total closure of bone defect, autogenous bone group had better bone repair after 90 days, followed by xenograft group that exhibited direct bone neoformation onto, and around, the particles confirming its osteoconductivity. In conclusion, cells from h-UCB and r-P were obtained, cultivated and osteodifferentiated in vitro and, the xenograft tested in vivo showed biocompatibility and osteoconductive potential in rat calvaria critical size defect